3 MHz Deep Radar Measurements South Pole - Troll Station (IPY 2008-2009) - Langley, Kirsty; Kohler, Jack; Dens, Ruben (Norwegian Polar Institute, 2016)
3 MHz Deep Radar Measurements along the route of the Norwegian – U.S. Scientific Traverse of East Antarctica 2008-2009. The primary goal of the deep radar was to measure ice thickness along the traverse route. In conjunction with surface elevation, the data also gives topography at the base of the ice sheet. Other useful aspects of the data are the clear internal layers and the ability to assess the presence or absence of water at the base of the ice sheet. ### Route - From: South pole [-90, 0] - Across: Recovery lakes region - To: Troll station [-72.01, 2.53] ### Instruments The pulse was generated by a Kentech GPR pulser emitting +/- 2kV at a PRF of 500-1000 Hz. At the receive end the signal was fed through a minicircuits RF Transformer 9:1 (16:1 was also tried), followed by an amplifier and into a picoscope dual channel digital oscilloscope. The oscilloscope was connected to a CF19 Panasonic toughbook for real time data viewing and data storage. Gecko, a program written and compiled by Rickard Pettersson was used to digitize, display and store the data. A Garmin handheld GPS was connected to the pc and gave position information for each trace. 12V, 55Ah gel cell batteries provided power to both the receive and the transmit electronics.